1997
DOI: 10.1159/000461954
|View full text |Cite
|
Sign up to set email alerts
|

Two Missense Mutations of H Type α(1,2)Fucosyltransferase Gene (FUT1) Responsible for Para-Bombay Phenotype

Abstract: Background and objectives: Rare individuals (Bombay and para-Bombay phenotypes) fail to express the A, B and H antigens on erythrocyte membranes because of a lack in the //gene (FUT1)-encoded α(l,2)fucosyltransferase activity. In this study, we have found a para-Bombay individual (B(m)^h) who expressed B and H antigens in saliva but not on red blood cells. The FUT1 alleles of this person contained two single base changes (T460C and G1042A) in the coding region relative to the wild type allele. These substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…Although the FUT2 locus has null alleles with high frequencies (about 0.5) in most populations of the world and has prevalent null alleles (se 428 and se 385 ; Kelly et al 1995;Koda et al 1996Koda et al , 2001bLiu et al 1998), the mutational character in the null allele of Dani populations is similar to that observed in FUT1, in which null alleles of the FUT1 locus (h alleles, the Bombay or para-Bombay phenotype in the ABO histo-blood group system) are rare and generated by different mutational events without prevalent null alleles (Kelly et al 1994;Koda et al 1997;Wagner and Flegel 1997;Wang et al 1997;FernandezMateos et al 1998;Wagner et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Although the FUT2 locus has null alleles with high frequencies (about 0.5) in most populations of the world and has prevalent null alleles (se 428 and se 385 ; Kelly et al 1995;Koda et al 1996Koda et al , 2001bLiu et al 1998), the mutational character in the null allele of Dani populations is similar to that observed in FUT1, in which null alleles of the FUT1 locus (h alleles, the Bombay or para-Bombay phenotype in the ABO histo-blood group system) are rare and generated by different mutational events without prevalent null alleles (Kelly et al 1994;Koda et al 1997;Wagner and Flegel 1997;Wang et al 1997;FernandezMateos et al 1998;Wagner et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Elmgren et al (1997) have reported, in their transfection study of a chimeric FUT3 construct containing T202 C or C314 T, that the T202 C mutation has about 10% activity compared with a construct containing the wild type allele, and that the C314 T construct has a similar activity to the wild type allele, whereas the construct containing both T202 C and C314 T has no activity. We have also reported two missense mutations (T460 C and G1042 A) of the H type α(1,2)fucosyltransferase gene (FUT1) in a Japanese individual with the para-Bombay phenotype (Wang et al 1997). Although the h 460,1042 FUT1 construct shows no activity after transfection into COS7 cells, the chimeric construct containing T460 C or G1042 A has about 1% or 10% activity compared with the construct containing the wild type FUT1 allele.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism for the deficiency of H and Se enzymes has been analyzed in many populations (Kelly et al 1994Koda et al 1996;Yu et al 1996;Kaneko et al 1997;Wang et al 1997;Wagner and Flegel 1997;Fernandez-Mateos et al 1998;Liu et al 1998bLiu et al , 1999b. These results have demonstrated that the frequency of H enzyme-deficient alleles is very low, and that there is no prevalent null allele, whereas the frequency of Se enzyme-deficient alleles is about 50% in all populations tested, and there are prevalent population-specific null alleles.…”
Section: Introductionmentioning
confidence: 99%